The integration process of the jesuit provinces in Spain. Some canonical and spiritual considerations - Etxeberría, S.J., Juan José (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
This paper deals with the experience lived during the past years with the reorganization of the Jesuit provinces in Spain from a spiritual, apostolic and legal point of view. Without any doubt, the integration process of the Provinces is a call to update our charisma and to drive our mission within current contexts, and thus, to remember the necessity to pay special attention to spiritual and apostolic issues. As a matter of fact, the Society of Jesus was born for a mission and with a mission. This unification of Provinces questions and opens us to the Ignatian magis, that is, it questions us about our capacity to better serve the mission within our service to the Church and to society. Furthermore, there is a need to take into consideration that structural changes and legal documents are necessary for these processes to take place, but always bearing in mind the revitalization of the life and mission of religious institutions. The development of different tools and legal documents has been of help and of use in the creation of the new Province of Spain.